Anatomia externa e esquelética de duas populações de Australoheros Rícan & Kullander, 2006 (Teleostei: Perciformes: Cichlidae) de áreas adjacentes das bacias dos Rios Doce e São Francisco - Gilmar Ferreira do Carmo (2013)
Specimens of two populations of angelfish of the genus Australoheros inhabiting adjacent basins were analysed, one from the Cipó river (São Francisco river basin, Serra do Cipó National Park) and another from the Santa Bárbara (Doce river basin, Peti Private Reserve), based on morphological characters external, morphometric, meristic, skeletal, ontogenetic, molecular. Initially, it was assumed that belonged to the same species, if studies with Astyanax tourmalinensis (Triques & Queiroz, 2010) and Trichomycterus brasiliensis (Fowler, 1954), described in a watershed and found in adjacent basins. However, clear qualitative, morphometric and allometric distinctions, the latter revealed by analysis of simple linear regression and covariance (ANCOVA), led to the hypothesis that they are not only species distinct from each other, but all their congeners. despite the limited scope of the work, the results corroborate the idea of endemism between adjacent basins and inside them. It also reinforces this same idea the fact that the two new species of the genus are clearly diagnosed from the others in regions where there were already described species. a characterization morphology was made for each population, as well as a diagnosis, relative to the proposition of new species. Molecular characterization was also carried out for the PNSC and A. ipatinguensis populations.